2020
DOI: 10.1002/wnan.1653
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked polymer nanocapsules for therapeutic, diagnostic, and theranostic applications

Abstract: Crosslinked polymer nanocapsules (CPNCs) are hollowed nanoparticles with network-like polymeric shells stabilized by primary bonds. CPNCs have drawn broad and significant interests as nanocarriers for biomedical applications in recent years. As compared with conventional polymeric nanoparticles systems without cavity and/or crosslinking architectures, CPNCs possess significant biomedical relevant advantages, including (a) superior structural stability against environmental conditions, (b) high loading capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…This formulation has been widely used to design an enhanced therapeutic enzyme platform for the treatment of metabolic diseases. [ 15 ] This novel architecture of the CT‐CPNC also motivated in‐depth discussions and thoughts into the fundamental mechanism of CT‐CPNC formation. Liu and co‐workers demonstrated through molecular simulation that the monomers (acrylamide, A1 ) were locally concentrated around each cargo, showing a peak concentration located 4–5 nm away from the cargo surface in an aqueous solution.…”
Section: Synthesismentioning
confidence: 93%
See 2 more Smart Citations
“…This formulation has been widely used to design an enhanced therapeutic enzyme platform for the treatment of metabolic diseases. [ 15 ] This novel architecture of the CT‐CPNC also motivated in‐depth discussions and thoughts into the fundamental mechanism of CT‐CPNC formation. Liu and co‐workers demonstrated through molecular simulation that the monomers (acrylamide, A1 ) were locally concentrated around each cargo, showing a peak concentration located 4–5 nm away from the cargo surface in an aqueous solution.…”
Section: Synthesismentioning
confidence: 93%
“…The particle size of CT‐CPNCs can be varied from 10–200 nm depending on the cargoes and synthesis conditions. [ 15 ] For example, single‐protein CT‐CPNCs with a small particle size (10–30 nm) usually have a long circulation half life in vivo, showing the potential for the treatment of metabolic diseases such as hyperuricemia [29b,50] . Blood–brain barrier (BBB) is a highly regulated brain endothelial structure, which provides shelter to the brain.…”
Section: Structures and Physicochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-targeted nanoparticles such as liposomal-based preparations [ 110 ] polymeric [ 111 ] and metallic nanoparticles [ 112 , 113 ] are readily available for the conjugation with antibodies and drugs, potentially opening the possibility to develop theragnostic (therapeutics and diagnostics) agents. These formulations can reduce the toxicity profiles of the payloads and improve the therapeutic widow.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…On the other hand, nanoparticles crosslinked by cellulose have received an increased attention in the agricultural sector due to their good stability under environmental conditions (Sun et al, 2020). For instance, stimuli-responsive nanocapsules based on cellulose modified with fatty acid (undec-10-enoic) loaded captan and pyraclostrobin were developed against apple canker (Neonectria ditissima), and the results showed that the active ingredients were released when triggered by the presence of cellulolytic fungi (Machado et al, 2021).…”
Section: Cellulose-based Nanopesticidesmentioning
confidence: 99%